Eastern Poland as the Borderland of the European Union - Komornicki, Tomasz; Miszczuk, Andrzej (Quaestiones Geographicae, 2010)
The purpose of the present paper is to characterise the socio-economic potentials of the regions situated on both sides of the Polish-Russian, Polish-Belarusian and Polish-Ukrainian boundaries (against the background of historical conditions), as well as the economic interactions taking place within these regions. The analysis, carried out in a dynamic setting, sought to identify changes that have occurred owing to the enlargement of the European Union (including those associated with the absorption of the means from the pre-accession funds and from the structural funds). The territorial reach of the analysis encompasses four Polish units of the NUTS 2 level (voivodeships, or "voivodeships"), situated directly at the present outer boundary of the European Union: Warmia-Mazuria, Podlasie, Lublin and Subcarpathia. Besides, the analysis extends to the units located just outside of the eastern border of Poland: the District of Kaliningrad of the Russian Federation, the Belarusian districts of Hrodna and Brest, as well as the Ukrainian districts of Volyn, Lviv and Zakarpattya.